Enhanced remediation of pollutants by microorganisms–plant combination - Supreeth, M. (Int J Environ Sci Technol (Tehran), 2021)
The pollutants have become ubiquitous in the total environment (water, soil and air) due to human activities and they are hazardous to all forms of life on the earth. This problem has made scientists focus on mitigating or complete reduction in pollutants by several means. Microorganism and plants are known to scavenge pollutants. Both are studied enormously in reducing, refining, and removing pollutants from the environment successfully. But, their slow process for removal is disadvantage. However, according to recent advancements in the abatement of pollutants, a combined system of both microorganisms and plant has shown to enhance the remediation of pollutants to an efficient level. In a nutrient-depleted pollutant-rich environment, when suitable plant and microorganisms are introduced, the plant interacts with the rhizosphere and root associate with microorganisms to survive in toxic conditions. The chemicals released by plants signal the microorganisms for interactions. This interaction leads in higher germination efficiency and enhanced root elongation which results in enhanced degradation of pollutants in both rhizosphere and phyllosphere. In this background, the current review article provides an overview of the recent advancement in microorganisms plant combined systems in enhanced removal of several recalcitrant pollutants. The conclusion highlights the challenges and future perspectives in this area of research.